2016
DOI: 10.24831/jai.v44i2.13491
|View full text |Cite
|
Sign up to set email alerts
|

Uji Ketahanan Anggrek Hibrida Phalaenopsis terhadap Penyakit Busuk Lunak yang Disebabkan oleh Dickeya dadantii

Abstract: ABSTRACT<br /><br />One of the most popular orchids and cultivated by Indonesia and other countries is Phalaenopsis. The main disease of Phalaenopsis orchids in Indonesia is soft rot caused by bacteria Dickeya dadantii. The purpose of this study was to know the resistanctcy of Phalaenopsis hybrid to soft rot disease. The experiment was conducted at the Bacterial Plant Laboratory, Department of Plant Protection, the Greenhouse of Leuwikopo, Bogor Agricultural University, and the plastic house of Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…All treatments showed the same pattern of AUPDC, and softrot symptom diameter, as shown in 'KHM 205', 1126, 1318, 2249. The result presented in this study confirmed that P. amboinensis was a more resistant genotype, as reported in the previous research (Firgiyanto et al 2016;Sukma et al 2017).…”
Section: Experiments 3: Phalaenopsis Amabilis Resistance Response To Ssupporting
confidence: 92%
See 2 more Smart Citations
“…All treatments showed the same pattern of AUPDC, and softrot symptom diameter, as shown in 'KHM 205', 1126, 1318, 2249. The result presented in this study confirmed that P. amboinensis was a more resistant genotype, as reported in the previous research (Firgiyanto et al 2016;Sukma et al 2017).…”
Section: Experiments 3: Phalaenopsis Amabilis Resistance Response To Ssupporting
confidence: 92%
“…Exogenous SA concentration is a critical matter regulating its function as a plant hormone. The 10 ppm SA concentration induced resistance in Phalaenopsis hybrid KHM 205 but did not induce resistance in KHM 1138 against D. dadantii infection (Firgiyanto et al 2016). Induction of Phalaenopsis amabilis resistance using high SA concentrations (≤85 ppm) can suppress the growth of Fusarium oxysporum in vitro (Noviantia 2016).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Pengendalian penyakit busuk lunak biasanya dilakukan dengan penyemprotan bakterisida, namun hal ini dapat mencemari lingkungan dan menurunkan kualitas tanaman karena sisa residu yang menempel pada permukaan tanaman (Firgiyanto et al, 2016). Penelitian ini dilakukan untuk mencari alternatif lain yang lebih ramah lingkungan dan efektif dalam mengendalikan penyakit busuk lunak antara lain dengan menginduksi ketahanan tanaman.…”
Section: Pendahuluanunclassified
“…Analisis aktivitas peroksidase dilakukan mengikuti metode Sukma et al (2008) dan Firgiyanto et al (2016). Sampel yang digunakan yaitu bagian ujung daun bibit anggrek yang tidak terkena gejala busuk, dipotong dari masing-masing tanaman dan digabung sebagai sampel komposit untuk setiap konsentrasi perlakuan AS.…”
Section: Keteranganunclassified